Analysis of Monocyte to Lymphocyte Ratio and Clinical Symptoms of Clinically Confirmed Pulmonary Tuberculosis New Case Patients Before Treatment and After Intensive Phase - Handoko, Basti; Arliny, Yunita; Priyanto, Herry; Andayani, Novita; Yanifitri, Dewi Behtri (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2025)
Background: Treatment evaluation of clinically confirmed pulmonary tuberculosis (TB) is limited to clinical symptoms and chest X-rays that tend to be subjective and no better than bacteriological examination. Monocytes and lymphocytes mediate the immunopathology of TB infection as a form of host defense that affects the systemic concentration of the body’s defense cells. The study assesses the monocyte-to-lymphocyte ratio (MLR) to evaluate TB treatment. Methods: Longitudinal prospective paired t-test with characteristics of clinically confirmed pulmonary TB new cases then compared to monocytes, lymphocytes, and monocyte-lymphocyte ratio (MLR) before administration of anti-tuberculosis drugs (ATD) and the end of the intensive phase. Results: In thirty clinically confirmed pulmonary TB patients before and after the anti-tuberculosis drug (ATD) there was no difference in monocytes pre 8.3 - post 8.5 (P=0.82), there was a difference in lymphocytes pre 17.8 - post 25.6 (P<0.05) that affected the MLR ratio value pre 0.57 - post 0.39 (P<0.05). Conclusion: This study identifies there is a significant difference in MLR before treatment and after the intensive phase of clinically confirmed pulmonary TB.